Report on professional attachment with Deloitte & Touche. - Goh, Kristine Yi Lin. (2008)
The following Professional Attachment (PA) Report relates to my experiences and the knowledge attained during my 10 weeks attachment with Deloitte & Touche (Singapore). The report includes an introduction of the firm, with special regards to its working culture and environment. Besides, it also recounts details of my audit experience in the firm and also the knowledge and skills I have picked up during the course of work. The report will then end off with recommendation to the attachment programme suggested for consideration.